Mortalidade por Covid-19 - Série de casos em uma capital da região norte do Brasil - Cruz, Vanessa Gomes da (Universidade Federal do Tocantins, 2024)
Objective: To analyze the profile of deaths, with mention of SARS-CoV-2 infection in the Death Certificate that occurred during 2020 in residents of the municipality of Palmas-TO. Materials and Methods: This is a case series mortality study. We analyzed 209 deaths that met the case definition (death of a resident in Palmas-TO, with laboratory, imaging or clinical- epidemiological confirmation for SARS-CoV-2 infection, which occurred in 2020). Data were collected from municipal epidemiological surveillance forms, arranged in a spreadsheet in Microsoft Excel 2019 and submitted to statistical analysis using the statistical software R version 4.2.2. Sociodemographic, anthropometric, clinical-epidemiological and hospitalization variables were analyzed. Results: Among the analyzed events, there was a concentration of cases in older adults (148; 70.8%), males (64.3%) and with low educational level (100; 47.8%). Signs and symptoms recorded were mainly respiratory distress (203; 97.1%), fever (157; 75.1%) and cough (69%). It was identified that 173 patients (82.8%) underwent mechanical ventilation. Only 8 cases did not present any reported comorbidity. The survival curve showed a gradual decline in the probability of survival over time, with median survival estimated at 20 days. Conclusion: COVID-19 was considered the main cause of death in the analyzed period, changing the municipality’s mortality profile. A higher frequency of deaths was observed among the elderly, men and people with comorbidities or risk factors for the worsening of COVID-19.